PENGARUH FOTOAUTOTROFIK TERHADAP PERTUMBUHAN TUNAS KRISAN DALAM PROSES KULTUR IN VITRO SERTA PERBEDAAN STOMATA INVITRO DAN EXVITRO KRISAN - Siti Hartati Yusida Saragih; Khairul Rizal; Kamsia Dorliana Sitanggang (JURNAL AGROPLASMA, 2020)
Chrysanthemum (Chrysanthemum indicum L.) is an ornamental plant that is included in an important contribution in the ornamental plant business. Related to chrysanthemum buds grown in vitro in culture tubes or bottles with a tightly closed to avoid bacterial and fungal contamination and to protect the humidity of the culture environment. However, this tight cap often affects the composition of the gas in a jar or bottle, which inhibits plant growth. The purpose of this study was to study the effect of photoautotrophic on the growth of chrysanthemum buds in the in vitro culture process and the differences in invitro and exvitro chrysanthemum stomata. This research was conducted in March 2016 to May 2016 in the Microtechnical Laboratory, IPB University. Research results obtained from research on the position given to research conducted on the number of roots, the number of books and the number of shoots. The influence of the environment of exvitro also significantly affects the number of stomata, stomata width and stomata density. Keywords :ex vitro,  in vitro, photoautotrophic